ANALISIS HAMBATAN PELAKSANAKAN PEMBELAJARAN DARING DALAM KEGIATAN BELAJAR MENGAJAR MATA PELAJARAN IPS PADA SISWA KELAS V SD - Sari, Indah Serlinda; Supriatna, Encep (Universitas Pendidikan Indonesia Kampus Serang, 2021)
This study aimed to determine the regulation of the implementation of online learning in teaching and learning activities for social studies subjects to fifth-grade elementary school students, the implementation of social studies online learning for fifth-grade elementary school students, and the inhibiting factors in the implementation of social studies online learning in grade five students. V elementary school. This research is qualitative. Data collection in this study used the method of observation and interviews with fifth-grade teachers and several fifth-grade students. Data analysis used qualitative data analysis techniques with inductive thinking. This research was conducted at MI Muhammadiyah Braja Asri. The results of this study are as follows: 1) Regulations on the implementation of online learning in teaching and learning activities for social studies subjects for fifth-grade elementary school students include: the application of the principle that anyone can become a teacher, learning with multidimensional student answers, the teacher is no longer a teacher. the only source of student learning, and the use of information and communication technology in supporting effective learning. 2) the implementation of online learning for social studies subjects for fifth-grade elementary school students, and 3) the inhibiting factors in the implementation of social studies online learning for fifth-grade elementary school students, including the inhibiting factors for the implementation of social studies online learning in fifth-grade teachers found several obstacles or difficulties in its implementation, including the teacher being less than optimal in delivering the material, the lack of student motivation in participating in learning and students having difficulty understanding and receiving the material.